"Reversible" photochromism of polyoxomolybdate–viologen hybrids without the need for proton transfer. Issue 1 (11th December 2018) - Li, Li; Wang, Jun-Ren; Hua, Yang; Guo, Yu; Fu, Chen; Sun, Ya-Nan; Zhang, Hong
Abstract : The "reversible" photochromism of polyoxomolybdate–viologen hybrids can be achieved without proton transfer, and the weak electron-withdrawing ability of viologen favors photoreduction of Mo(vi ). Abstract : A case study of two new covalently bonded polyoxomolybdate–viologen hybrids revealed that "reversible" photochromic properties can be achieved without the need for proton transfer, and the weak electron-withdrawing ability of the coordinated ligand favors photoreduction of Mo(vi ) to Mo(v ).